"He Didn't Add More Evidence": Using Historical Graphic Novels to Develop Language Learners' Disciplinary Literacy - Park, Jie Y. (Journal of adolescent & adult literacy, 2016)
A growing body of work has contributed to the theorizing and practice of disciplinary literacy instruction at the secondary level. However, there has been relatively little attention paid to pedagogical supports—texts and practices—that can foster historical literacy development in English learners who begin their U.S. schooling in middle or high school. Using discourse data collected from an after‐school literacy program, the author shows how a historical graphic novel can foster disciplinary literacy by helping students approach history as an account. She posits that in order for students to ponder authorial choices, question representations, and grapple with considerations of truthfulness, they have to understand that what they are reading is an account of history—a person's interpretation and construction of the past. The study's findings have implications for practitioners and researchers interested in the intersections of English learners, graphic novels, and disciplinary literacy in history.